2006
DOI: 10.1007/s00438-006-0158-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of the transposable element Ac/Ds in conjunction with Spm/dSpm for gene tagging allows extensive genome coverage with a limited number of starter lines: functional analysis of a four-element system in Arabidopsis thaliana

Abstract: We have developed a novel four-element based gene tagging system in Arabidopsis to minimize the number of starter lines required to generate genome-wide insertions for saturation mutagenesis. In this system, the non-autonomous cassette, Ds(dSpm), comprises of both Ds and dSpm elements cloned one within the other along with appropriate selection markers to allow efficient monitoring of excision and re-integration of the transposons. Trans-activation of the outer borders (Ds) and selection against the negative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Coupland et al (1989) had shown that 209 bp of the Ac 3 0 -end and 238 bp of the 5 0 -end are sufficient to enable Ds excision at frequencies comparable to that of longer Ac ends, in tobacco. The negative selection marker gene 2 0 -iaaH from plasmid pAJ6 (Panjabi et al 2006) was cloned between the reversed ends of the Ds element. An EcoRI-BamHI fragment containing a bacterial origin-ofreplication (ori) and the b-lactamase (bla) gene from pBR322 (New England Biolabs, Beverly, MA) was cloned adjacent to the 5 0 -Ds end to facilitate plasmid rescue of the T-DNA insertion locus in the plant genome.…”
Section: Methodsmentioning
confidence: 99%
“…Coupland et al (1989) had shown that 209 bp of the Ac 3 0 -end and 238 bp of the 5 0 -end are sufficient to enable Ds excision at frequencies comparable to that of longer Ac ends, in tobacco. The negative selection marker gene 2 0 -iaaH from plasmid pAJ6 (Panjabi et al 2006) was cloned between the reversed ends of the Ds element. An EcoRI-BamHI fragment containing a bacterial origin-ofreplication (ori) and the b-lactamase (bla) gene from pBR322 (New England Biolabs, Beverly, MA) was cloned adjacent to the 5 0 -Ds end to facilitate plasmid rescue of the T-DNA insertion locus in the plant genome.…”
Section: Methodsmentioning
confidence: 99%
“…The 'carrier' is used to generate insertions in the genome that are subsequently used as the donor sites for transposition of the 'jumper' element. In plant genetics, such donor sites, usually called 'launch pads', have successfully been used to saturate specific regions of the genome with insertions [ 16 , 31 , 32 ]. Because zebrafish exons are small, the mutagenesis efficiency of this approach is expected to be low.…”
Section: Mutagenesis Of Closely Linked Genes By Re-mobilization Of Gementioning
confidence: 99%
“…Unlike retroviral insertions, transposons can be re-mobilized in order to obtain exon insertions or to generate flanking deletions (Figure 1 ). Re-transposition also offers a unique approach to reducing the size of insertion libraries - the 'launch pad' strategy [ 16 , 32 ]. A relatively small collection of the launch pads (Figure 1 ) regularly distributed throughout the genome must be generated and deposited in a stock center.…”
Section: Large-scale Reverse Genetics Mutagenesis In Fishmentioning
confidence: 99%